Using a retention in care protocol to promote positive health and systems related outcomes*. (14th December 2018) - Larbi, Alfred A.; Spielberg, Freya; Kamanu Elias, Nnemdi; Athey, Erin; Ogbuawa, Ngozi; Murphy, Nancy
ABSTRACT: People living with HIV can experience the full benefits of retention when they are continuously engaged in care. Continuous engagement in care promotes improved adherence to ART and positive health outcomes. An infectious disease clinic has implemented a protocol to primarily improve patient retention. The retrospective, facility-based, costing study took place in an infectious disease clinic in Washington DC. Retention was defined in two ways and over a 12-month period. Micro-costing direct measurement methods were used to collect unit costs in time series. Return on investment accounted for the cost of treatment based on CD4 strata. ROI was expressed in 2016USD. The difference in CD4 and viral load levels between the two periods of analysis were determined for active patients, infected with HIV. The year before the intervention was compared to the year of the intervention. Total treatment expenditure decreased from $2, 435, 653.00 to $2, 283, 296.23, resulting in a $152, 356.77 gain from investment for the healthcare system over a 12-month investment period. The viral load suppression rate increased from 81 to 95 ( p  = 0.04) over the investment period. The number of patients in need of HIV related opportunistic infection prophylaxis decreased from 21 to 13 ( p  = 0.06). Improved immunologic, virologic and healthcare expenditure outcomes can be linked to the quality of retention practice.